The Influence of Company Image, Products, on Purchasing Decisions through Customer Satisfaction in the Shipbuilding Industry (Case Study at Pt Pal Indonesia) - Sarifin, Miftachus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the factors that influence customer satisfaction, reputation and customer company offerings in the shipbuilding industry. This research takes a case study at the largest shipyard in Indonesia, namely PT PAL Indonesia. The sample population used a census method taken from all of the Company's marketing staff, totaling 30 people, who processed the data using SPSS. Research findings show that although company image influences customer satisfaction and purchasing decisions, product image influences customer satisfaction and company image, and product image has nothing to do with purchasing decisions. through customer satisfaction.